Variation in Photosynthetic Performance Relative to Thallus Microhabitat Heterogeneity in Lithothamnion australe (Rhodophyta, Corallinales) Rhodoliths. Issue 1 (21st November 2020) - Kim, Ju‐Hyoung; Steller, Diana L.; Edwards, Matthew S.
Abstract : Rhodoliths are free‐living, coralline algae that create heterogeneous structure over sedimentary habitats. These fragile ecosystems are threatened by anthropogenic disturbances that reduce their size and three‐dimensional structural complexity. We investigated how physical disturbance from boat moorings affects photosynthetic performance in the rhodolith Lithothamnion australe. Photosynthetic parameters were measured for intact rhodoliths and crushed rhodolith fragments of two sizes (ca. 1 and 2 cm diameter), while chlorophyll fluorescence was measured at the surface of rhodoliths of these two sizes, between the interior branches of the larger rhodoliths, and at the surface of 52 various sized (0.4–3.5 cm diameter) rhodoliths. Gross productivity and net productivity were 15% and 36% higher, respectively, in the smaller L. australe, while respiration was 10% higher in the larger individuals. Thallus crushing reduced gross productivity by 20% and 41%, and net productivity by 9% and 14% in the smaller and larger rhodoliths, respectively. It also reduced respiration by 33% and 60% in the smaller and larger rhodoliths, respectively. Fluorescence parameters were all greater at the surface of the larger L. australe than the smaller individuals, and greater at the surface than in the interior parts of the larger individuals. Across a range of rhodolith sizes, surface fluorescence parameters were at their maxima in 1.54 to 2.32 cm diameter individuals. These results show that L. australe 's complex structure creates heterogeneity in photosynthesis and respiration between their surface and interior parts and among rhodolith sizes. This information can help predict how rhodoliths may respond to disturbance and environmental stressors.